Interplay between CMVs and interferon signaling: implications for pathogenesis and therapeutic intervention. (November 2012) - Trilling, Mirko; Le, Vu Thuy Khanh; Hengel, Hartmut
Most human individuals are latently infected with human CMV, a prototypic β-herpesvirus, frequently acquired during early childhood. In the absence of adequate immune control, the otherwise asymptomatic infection causes life-threatening disease. To enable efficient replication and to maintain lifelong latency in immunocompetent hosts, CMVs have evolved numerous molecules mediating immune evasive properties, targeting both innate and adaptive immune responses. Upon infection, cells secrete interferons (IFNs), which initiate an extremely fast signal transduction cascade upon binding to their cognate receptors, culminating in a pronounced change in the cellular gene expression profile. This response leads to the establishment of an intracellular antimicrobial state and to the recruitment, as well as stimulation, of the adaptive immune system. Unfortunately, CMVs impede the IFN system by interfering with its induction, signaling and downstream effector functions. This review aims to present our current understanding of such cytomegaloviral IFN-evasive properties, their pathogenic implications and potential for therapeutic exploitation.